DESIGN OF RC DEEP BEAMS AS PER INDIAN, EUROPEAN AND AMERICAN CODES OF PRACTICE - kumar, Mr.K.Dinesh; Subathra, Ms.S. (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
Provisions of Indian (IS 456: 2000), European (EC2 - 1992) and American (ACI - 318) codes of practice for the design of RC deep beams have been critically studied and reported. As per the recommendations of these codes, RC deep beams have been designed adopting limit state method. The quantities of concrete and steel and the total cost of deep beams for three different spans have been calculated and are compared using bar chart.